Central Nervous System-Endogenous TLR7 and TLR9 Induce Different Immune Responses and Effects on Experimental Autoimmune Encephalomyelitis - Dieu, Ruthe Storgaard; Wais, Vian; Sørensen, Michael Zaucha; Marczynska, Joanna; Dubik, Magdalena; Kavan, Stephanie; Thomassen, Mads; Burton, Mark; Kruse, Torben; Khorooshi, Reza; Owens, Trevor (Frontiers in Neuroscience, 2021)
Innate receptors, including Toll like receptors (TLRs), are implicated in pathogenesis of CNS inflammatory diseases such as multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE). TLR response to pathogens or endogenous signals includes production of immunoregulatory mediators. One of these, interferon (IFN)β, a Type I IFN, plays a protective role in MS and EAE. We have previously shown that intrathecal administration of selected TLR ligands induced IFNβ and infiltration of blood-derived myeloid cells into the CNS, and suppressed EAE in mice. We have now extended these studies to evaluate a potential therapeutic role for CNS-endogenous TLR7 and TLR9. Intrathecal application of Imiquimod (TLR7 ligand) or CpG oligonucleotide (TLR9 ligand) into CNS of otherwise unmanipulated mice induced IFNβ expression, with greater magnitude in response to CpG. CNS extraparenchymal CD45+ cells were identified as source of IFNβ. Intrathecal CpG induced infiltration of monocytes, neutrophils, CD4+ T cells and NK cells whereas Imiquimod did not recruit blood-derived CD45+ cells. CpG, but not Imiquimod, had a beneficial effect on EAE, when given at time of disease onset. This therapeutic effect of CpG on EAE was not seen in mice lacking the Type I IFN receptor. In mice with EAE treated with CpG, the proportion of monocytes was significantly increased in the CNS. Infiltrating cells were predominantly localized to spinal cord meninges and demyelination was significantly reduced compared to non-treated mice with EAE. Our findings show that TLR7 and TLR9 signaling induce distinct inflammatory responses in the CNS with different outcome in EAE and point to recruitment of blood-derived cells and IFNβ induction as possible mechanistic links between TLR9 stimulation and amelioration of EAE. The protective role of TLR9 signaling in the CNS may have application in treatment of diseases such as MS.